Respuesta :

Answer:

a = 6, b = -12, c = 0

Step-by-step explanation:

General form of a quadratic equation is:

ax² + bx + c = 0

6x² = 12x

6x² - 12x = 0

6x² - 12x + 0 = 0

(no constant means it's 0)

Comparing to the general form:

a = 6, b = -12, c = 0

The value of a = 6, b = -12, c = 0

  • The calculation is as follows:

we know that

The general form of a quadratic equation is:

[tex]ax^2 + bx + c = 0[/tex]

[tex]6x^2 = 12x\\\\6x^2 - 12x = 0\\\\6x^2 - 12x + 0 = 0[/tex]

Here no constant means it's 0

So,

a = 6, b = -12, c = 0

learn more: https://brainly.com/question/994316?referrer=searchResults

ACCESS MORE